Big Mother: The Internet of Performance Thingies. Issue 4 (April 2017) - Honebein, Peter C.
Abstract : The Internet of performance thingies, behavioral economics, and social physics are disrupting the field of human performance technology (HPT). By balancing these young Turks with our old standards of behavior engineering, we can make HPT more useful and meaningful to our clients and organizations.